1966
DOI: 10.1037/h0023693
|View full text |Cite
|
Sign up to set email alerts
|

Responses to feminine odors in normal and castrated male rats.

Abstract: Following a 50-day period of cohabitation with females, 36 male rats were tested in their home cages for sexual vigor and for preference for odors from normal receptive vs. nbiireceptive females. 2 mo. prior to odor preference testing, 13 sexually active and 6 inactive Ss were castrated; 12 active and 5 inactive Ss served as controls. Active normal Ss preferred receptive-female ; odor over nonreceptive-female odor (p < .01), but inactive normal Ss and castrates showed no preference for either feminine odor. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(41 citation statements)
references
References 1 publication
5
36
0
Order By: Relevance
“…As NE in the OB and frontal cortex serve distinct functions, the differential regulations in these two areas by androgens imply unique biological importance for both regions. For the OB, behavioral studies have shown that castration reduces preferences of male rats to estrous females (Carr et al, 1966), conspecific odors (Carr et al, 1965;Brown, 1977), as well as disrupting the male rats' dishabituation (memory/recognition) responses to female chemical cues (Guan and Dluzen, 1994). Both preference and memory/recognition responses appear to involve the OB-NE system (Gray et al, 1986;Sullivan et al, 1989Sullivan et al, , 1991Cornwell-Jones, 1988;Guan et al, 1993a,b;Shang and Dluzen, 1998b).…”
Section: Discussionmentioning
confidence: 89%
“…As NE in the OB and frontal cortex serve distinct functions, the differential regulations in these two areas by androgens imply unique biological importance for both regions. For the OB, behavioral studies have shown that castration reduces preferences of male rats to estrous females (Carr et al, 1966), conspecific odors (Carr et al, 1965;Brown, 1977), as well as disrupting the male rats' dishabituation (memory/recognition) responses to female chemical cues (Guan and Dluzen, 1994). Both preference and memory/recognition responses appear to involve the OB-NE system (Gray et al, 1986;Sullivan et al, 1989Sullivan et al, , 1991Cornwell-Jones, 1988;Guan et al, 1993a,b;Shang and Dluzen, 1998b).…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies (Brown, 1977;Carr et al, 1966;Ferkin, 1992;Nyby et al, 1977), usually carried out in rodent species, showed that mammals reliably choose to approach and investigate pheromonal cues from an opposite-sex, as opposed to a same-sex, conspecific. Typically, these sex-specific odor preferences are only expressed during the breeding season, in the presence of circulating testosterone (males) or ovarian steroids (females).…”
Section: Sex Differences In Sexual Partner Preference: Contribution Omentioning
confidence: 99%
“…Carr et al 1966, Rajska--Jurgiel 1976, Reich and Tamarin 1980, Chitty 1986. It was also shown that olfactory interactions between related species are possible (Drickamer 1984).…”
Section: Discussionmentioning
confidence: 99%